Synthesis of a new vanadyl(IV) complex with trehalose (TreVO): insulin-mimetic activities in osteoblast-like cells in culture - Barrio, Daniel Alejandro (2003)
Vanadium compounds show interesting biological and pharmacological properties. Some of them display insulin-mimetic effects and others produce antitumor actions. The bioactivity of vanadium is present in inorganic species like the vanadyl(IV) cation or vanadate( V) anion. Nevertheless, the development of new vanadium derivatives with organic ligands which improve the beneficial actions and decrease the toxic effects is of great interest. On the other hand, the mechanisms involved in vanadium bioactivity are still poorly understood. A new vanadium complex of the vanadyl(IV) cation with the disaccharide trehalose (TreVO), Na6 [VO(Tre)2].4H2O, here reported, shows interesting insulin- mimetic properties in two osteoblast cell lines, a normal one (MC3T3E1) and a tumoral one (UMR106). The complex affected the proliferation of both cell lines in a different manner. On tumoral cells, TreVO caused a weak stimulation of growth at 5 lM but it inhibited cell proliferation in a dose-response manner between 50 and 100 lM. TreVO significantly inhibited UMR106 differentiation (15–25% of basal) in the range 5–100 lM. On normal osteoblasts, TreVO behaved as a mitogen at 5–25 lM. Different inhibitors of the MAPK pathway blocked this effect. At higher concentrations (75–100 lM), the complex was a weak inhibitor of the MC3T3E1 proliferation. Besides, TreVO enhanced glucose consumption by a mechanism independent of the PI3-kinase activation. In both cell lines, TreVO stimulated the ERK phosphorylation in a dose- and time-dependent manner. Different inhibitors (PD98059, wortmannin, vitamins C and E) partially decreased this effect, which was totally inhibited by their combination. These results suggest that TreVO could be a potential candidate for therapeutic treatments.